Characterization of Textile Industrial Effluents and its Effects on Aquatic Macrophytes and Algae - Roy, R; Fakhruddin, ANM; Khatun, R; Islam, MS; Ahsan, MA; Neger, AJMT (Bangladesh Journal of Scientific and Industrial Research, 2010)
Textile industries release huge amount of effluents to aquatic systems, which contain toxic and hazardous pollutants degrading the environment. A laboratory scale study was conducted to characterize physicochemical parameters of local textile industrial effluents and evaluate their impact on aquatic macrophytes and algae. Total suspended solids (TSS) and total dissolved solid (TDS) was found 100 to 336 mg/L and 1856 to 4356 mg/L, respectively. The recorded pH was 9.6 to 11.2 and temperature 40.5 to 43°C. Dissolved oxygen (DO), biological oxygen demand (BOD) and chemical oxygen demand (COD) was recorded 0.11 to 0.5, 151.24 to 299.1 and 652.8 to 2304 mg/L, respectively. Electrical conductivity (EC) was monitored 2210 to 6020 μs/cm; salinity was found 1.1 to 3.3 ‰, and color 1890.75 to 5625 PCU. Zinc (Zn), cadmium (Cd), copper (Cu) were 0.0838 to 0.596, 0.0 to 0.0006, 0.018 to 0.1727 ppm, respectively. Except heavy metals concentrations all of the physicochemical parameters were found beyond the standard limit set by department of Environment (DoE). Textile industrial effluents showed the toxic effects on aquatic macrophytes and algae, as aquatic macrophytes could hardly survive 2 days on textile effluents and noticeable reduction of algal concentration was found when grown on textile effluents. Key words: Textile effluents; Toxic effects; Physicochemical parameter; Aquatic macrophytes; Algae DOI: 10.3329/bjsir.v45i1.5187 Bangladesh J. Sci. Ind. Res. 45(1), 79-84, 2010